2016
DOI: 10.1016/j.jobcr.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of nonabsorbable and absorbable barrier membranes in periodontal osseous defects by guided tissue regeneration

Abstract: Both nonabsorbable and absorbable barrier membranes were equally effective in treating grade II buccal furcation defects in lower molars when used in conjunction with G-Graft except with respect to horizontal bone fill in which absorbable barrier membrane showed better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
14
0
3
Order By: Relevance
“…From the first GTR procedures described in the 1950s to nowadays, a need to find the ideal biomaterial for each case has existed; from a small periodontal regeneration where simple resorbable membrane are used, to vast defects where a titanium mesh should be placed ( 1 , 3 , 4 ). Today, the use of a resorbable membrane is extended in the clinical practice compared to the non-resorbable membranes such as expanded polytetrafluorethylene membrane (ePTFE) ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the first GTR procedures described in the 1950s to nowadays, a need to find the ideal biomaterial for each case has existed; from a small periodontal regeneration where simple resorbable membrane are used, to vast defects where a titanium mesh should be placed ( 1 , 3 , 4 ). Today, the use of a resorbable membrane is extended in the clinical practice compared to the non-resorbable membranes such as expanded polytetrafluorethylene membrane (ePTFE) ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have for some materials the proof of principle, through histological studies, that true periodontal regeneration can occur. This is the case for demineralized freeze‐dried bone allograft (DFDBA; Bowers et al., ) and bovine‐derived bone xenograft (BDX; Mellonig, ), among BS, and for other biomaterials, for example, enamel matrix derivatives (EMD) (in periodontal defects Mellonig, ; Yukna & Mellonig, ; Esposito, Grusovin, Coulthard, & Worthington, ), or different types of membranes (Kaushal, Kumar, Khan, & Lal, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that it acts as a good vehicle to transport different types of cells where total resorption provides a space for complete graft remodeling and bone tissue regeneration . The collagen membranes were used to protect the cells within the vehicle material in the early phases of periodontal healing in order to provide the best circumstances for regeneration . It is assumed that autologous gingival fibroblasts and their associated GMSC derived from gingival tissue are more superior and applicable option than that of allogeneic cell lines that was reported to be immunologically rejected by the recipient …”
Section: Discussionmentioning
confidence: 99%